CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND PULMONARY REHABILITATION: AWARENESS AMONG THE PATIENTS - Javaid, Muhammad Arslan; Amir, Muhammad; Faheem, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of awareness among the patients with Chronic Obstructive Pulmonary Disease (COPD) about the disease and pulmonary rehabilitation.Study Design: Cross sectional study.Place and Duration of Study: Department of Medicine, Combined Military Hospital (CMH), Multan, from Sep 2015 to Feb 2016.Methodology: A total of 115 patients diagnosed as Chronic Obstructive Pulmonary Disease, including both males and females and meeting the inclusion criteria were selected. Outcome variables were awareness regarding Chronic Obstructive Pulmonary Disease and the pulmonary rehabilitation. Demographic data and outcome variables were recorded on specially designed questionnaire.Results: Level of awareness regarding the disease was below average in 75 (65.2%) of the patients while average level of awareness was observed in 40 (34.8%) of our study cases. None of our study cases presented with level of awareness more than 66%. Level of awareness regarding pulmonary rehabilitation was below average in 98 (85.2%) while it was average in only 17 (14.8%) of our study cases and none of them had awareness more than 66%. Conclusion: The awareness regarding the disease and pulmonary rehabilitation was poor in our patients.